Pemanfaatan Paradigma Teknologi Tepat Guna dalam Desain Produk: Sebuah Kajian Literatur - Wildan Aulia; Imam Santosa; Muhammad Ihsan; Adhi Nugraha (Aliansi Desainer Produk Industri Indonesia (ADPII), 2023)
This article uses the appropriate technology paradigm in design activities as problem finding and internal potential tracking as the basis for design solutions. Appropriate technology is based on the real needs of the community, not on technological developments. This activity emphasizes how to provide a solution to a problem in community by bridging it to the appropriate technology. Its application is contextual according to the local conditions of the community. This principle is still relevant in relation to today's issues which view community diversity as an internal potential in dealing with broader problems. One of these can be seen from the principles of the Sustainable Development Goals (SDGs), which view development based on local conditions and culture as motivation. The contextuality of problems in the community and how to approach them underlies the general framework of this article by noting that sharing knowledge with the community is a way to understand their internal potential. This article attempts to offer the fit design term based on the appropriate technology paradigm by trying to define the key concepts of the term. This article uses the systematic literature review (SLR) method with related articles on appropriate technology practices from the ScienceDirect and MDPI databases. The concept is built based on the understanding that specific problems in the community are contextual in nature, oriented to local management, and optimize the diversity of the community and environmental potentials. Thus, the notion of appropriateness in this article is not interpreted narrowly in the context of tools, but rather leads to appropriateness. The key concept offered is that the design must be appropriate to the situation, related to certain circumstances, compatible, acceptable, and strengthening the community, and must be in accordance with the required objectives.